Adaptation of child and adolescent worry scale (caws) in Bangla - Haque, Mahjabeen (Dhaka University Journal of Biological Sciences, 2022)
The present study aimed to adapt the Child and Adolescent Worry Scale (CAWS) to use in the context of Bangladesh. The original scale developed by Campbell and Rapee in 1994 consisted of 20 items and higher scores on the scale indicate higher anxiety. Standard procedure for adaptation was followed. Item analysis was done on school going 130 mainstream and special need children aged between 6 to 15 years. The Cronbach’s Alpha and test-retest reliability was found to be .799 and .858 respectively for the adapted scale indicating high level of reliability. Criterion-related validity was measured by calculating concurrent and postdictive validity. Concurrent validity was measured by computing correlation (r= .912, p=.001) between the adapted scale and Beck Anxiety Inventory. Similarly, correlation value of postdictive validity was found to be .806, p=.001. Both measures ensured that the adapted scale measures the same construct as the original one. Moreover, the Mann-Whitney U test also indicated that the scale could differentiate between the mainstream and special need children regarding their worry/anxiety. Worry score was greater for the special need children than the other group (U= 608.50 at p =.001). It indicates that the adapted scale has good sensitivity to varying levels of anxiety severity. The psychometric properties of the Bangla CAWS suggest that professionals and the researchers can use the scale to assess children and adolescent’s overall level of anxiety in Bangladeshi context. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 417-427, 2022 (June)